Objective assessment of cognitive fatigue: a bibliometric analysis - Han, Jia-Cheng; Bai, Ke; Zhang, Chi; Liu, Na; Yang, Guan; Shang, Yu-Xuan; Song, Jia-Jie; Su, Dan; Hao, Yan; Feng, Xiu-Long; Li, Si-Rui; Wang, Wen (Frontiers in Neuroscience, 2024)
AimThe objective of this study was to gain insight into the nature of cognitive fatigue and to identify future trends of objective assessment techniques in this field.MethodsOne thousand and eighty-five articles were retrieved from the Web of Science Core Collection database. R version 4.3.1, VOSviewer 1.6.20, CiteSpace 6.2.R4, and Microsoft Excel 2019 were used to perform the analysis.ResultsA total of 704 institutes from 56 countries participated in the relevant research, while the People’s Republic of China contributed 126 articles and was the leading country. The most productive institute was the University of Gothenburg. Johansson Birgitta from the University of Gothenburg has posted the most articles (n = 13). The PLOS ONE published most papers (n = 38). The Neurosciences covered the most citations (n = 1,094). A total of 3,116 keywords were extracted and those with high frequency were mental fatigue, performance, quality-of-life, etc. Keywords mapping analysis indicated that cognitive fatigue caused by continuous work and traumatic brain injury, as well as its rehabilitation, have become the current research trend. The most co-cited literature was published in Sports Medicine. The strongest citation burst was related to electroencephalogram (EEG) event-related potential and spectral power analysis.ConclusionPublication information of related literature on the objective assessment of cognitive fatigue from 2007 to 2024 was summarized, including country and institute of origin, authors, and published journal, offering the current hotspots and novel directions in this field.